Digital Archive Management of Polri SuperApp Online SKCK: An Efficiency Evaluation of Information Retrieval Based on ISO 16175-1:2020 - Taufik Asmiyanto; Khairunnisa, Khairunnisa (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study evaluates the application of the ISO 16175-1:2020 standard in improving digital archive management within the online Police Record Certificate (SKCK) system integrated into the Polri SuperApp at the Bener Meriah Resort Police. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings show that the Polri SuperApp meets most of the functional requirements outlined in ISO 16175-1:2020, particularly in the areas of record creation, discovery, use, access control, and processes related to duplication and redaction. The system effectively enhances information retrieval efficiency through its comprehensive metadata-driven search capabilities and strengthens data security through two-factor authentication, encryption mechanisms, and detailed activity logs. However, the research also identifies notable limitations, especially in terms of system interoperability. The lack of seamless integration between the Polri SuperApp and external systems restricts efficient data exchange. Furthermore, features related to search result personalization and external collaboration require further development. Overall, the study concludes that the Polri SuperApp has made a positive contribution to transparent and accountable digital archive management in public services. Nonetheless, more extensive system integration and functional enhancement are necessary to achieve optimal information retrieval efficiency and fully support public service delivery.